PENGELOLAAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN ALAT PERAGA BENDA MANIPULATIF - Marjuki Marjuki (Manajer Pendididikan, 2017)
The purpose of this study is to get a picture of the responses and interests of students to the management of mathematics learning using Manipulative Objects. The research was conducted using a classroom action research approach. The research subjects of fourth grade students of SD Negeri 09 Kepahiang. Based on the results of research can be obtained average formative value of students from cycle I with an average value of 55.6, cycle II with an average value of 74.8 Average formative value of students from cycles I and II with a value of 65.2, while the average value of group I cycle with the value of 81 and cycle II with the value 93.3 The average value of the group of cycles I and II is 87.15.